Synthetic Lubricants Derived from Plastic Waste and their Tribological Performance. Issue 19 (16th June 2021) - Hackler, Ryan A.; Vyavhare, Kimaya; Kennedy, Robert M.; Celik, Gokhan; Kanbur, Uddhav; Griffin, Philip J.; Sadow, Aaron D.; Zang, Guiyan; Elgowainy, Amgad; Sun, Pingping; Poeppelmeier, Kenneth R.; Erdemir, Ali; et al.
Abstract: The energy efficiency, mechanical durability, and environmental compatibility of all moving machine components rely heavily on advanced lubricants for smooth and safe operation. Herein an alternative family of high‐quality liquid (HQL) lubricants was derived by the catalytic conversion of pre‐ and post‐consumer polyolefin waste. The plastic‐derived lubricants performed comparably to synthetic base oils such as polyalphaolefins (PAOs), both with a wear scar volume (WSV) of 7.5×10 −5 mm −3 . HQLs also performed superior to petroleum‐based lubricants such as Group III mineral oil with a WSV of 1.7×10 −4 mm −3, showcasing a 44 % reduction in wear. Furthermore, a synergistic reduction in friction and wear was observed when combining the upcycled plastic lubricant with synthetic oils. Life cycle and techno‐economic analyses also showed this process to be energetically efficient and economically feasible. This novel technology offers a cost‐effective opportunity to reduce the harmful environmental impact of plastic waste on our planet and to save energy through reduction of friction and wear‐related degradations in transportation applications akin to synthetic oils. Abstract : Lucrative lubricants : Chemical recycling through catalytic hydrogenolysis of waste plastics produces monodisperse oils similar in size and structure to industrial lubricants. These high‐quality liquids perform superior to traditional mineral oil lubricants with up to 43 % less wear during tribological testing. Preliminary techno‐economic and life cycle analyses find conversion of waste plastics to lubricants to be economically viable without the need for sorting.